Favorable immune recovery and low rate of GvHD in children transplanted with partially T cell-depleted PBSC grafts - Seitz, Christian; Greil, Johann (Bone marrow transplantation, 2019)
Transplantation of peripheral blood stem cells (PBSC) from matched unrelated donors (MUD) is still associated with a significant risk for graft vs. host disease (GvHD), especially in pediatric patients receiving grafts from adult donors containing high amounts of T cells. Here, we present long-term follow-up results on 25 pediatric patients, (acute leukemia n = 15, NHL n = 3, CML n = 3, MDS n = 5), transplanted with CD34 or CD133 positively selected PBSC from MUDs supplemented with an add-back of 1 × 107/kg body weight (kgBW) unselected T cells resulting in a median T-cell depletion (TCD) of 1.97 log. A total of 24/25 (96%) patients had primary engraftment. Early T-cell recovery was significantly improved compared to patients receiving CD34-selected grafts without T-cell add-back and similar to patients receiving unmanipulated bone marrow. GvHD incidence was low with 8/4% aGvHD grade II/III, no grade IV and 13% limited cGvHD. In total, 16/25 (64%) patients are alive after a median follow-up of 10 years. Five-year event-free survival (EFS) was 68%, relapse probability 24% and transplantation-related mortality (TRM) 12%. Thus, in PBSC allotransplants from MUD, partial TCD with serotherapy and CSA/MTX prophylaxis, can effectively reduce GvHD without hampering engraftment and immune reconstitution.